“Meek Russian Genius”: Reception of Andrei Platonov’s Prose in the Diaries of G.I. Alekseev - Galina N. Boeva (Studia Litterarum)
On the material of the diary prose of the Leningrad poet, prose writer, and artist G.I. Alekseev (1932–1987), the article traces his perception of the personality and work of Andrei Platonov. The author of the diary could get acquainted with Platonov’s prose in the late 50s or early 60s. References to Platonov have been found in the diary since 1963. They relate either to the literary fate and reputation of the writer, or his attitude, manifested in style. Platonov invariably appears among the best stylists-prose writers of the 20th century. Alekseev, a Leningrad free verse writer, not recognized by the professional community, projects his reflections on the literary fate of Platonov onto his own life in literature. In his notes, Alekseev fixes such features of Platonov’s poetics as childishness, even infantilism, and at the same time the wisdom of looking; “childish freshness of language” despite the fact that “the words are all old”; addressing the main issues of being (good and evil, life and death); special interest in the problem of human mortality and its overcoming. “Intimacy,” the ability to see through everyday life, “bewilderment before being,” persistent asking of questions — all this makes Alekseev one of Platonov’s followers, not at the level of imitation, but at the level of community of the aesthetic and ideological platform. Platonov became a landmark for many writers who overcame socialist realism, and Alekseev is among them.